Changes in the Interpretation of The Hadith of Anti-Tafsir Ra`yi and Its Impact on The Way Mufassirs Interpret the Qur`an - Dadang Darmawan (Diroyah : Jurnal Studi Ilmu Hadis, 2023)
Several hadiths forbid the use of ra'yi in interpreting the Quran. This prohibition created a taboo for interpreting Quran with ra'yi. These hadiths are the main focus of this research. The purpose of this study was to trace the quantity and quality of hadith anti tafsir ra'yi. This study also intends to trace changes in the interpretation of these hadiths. The methods used in this study are takhrij hadith and intellectual history. We analysed the collected data using Hegelian and Foucaultian approaches. This research found that none of the hadiths of anti-tafsir ra'yi was sahih. However, these hadiths are very popular and widely accepted and practised. The study also found that the interpretation of the hadiths of anti-tafsir ra'yi has changed four times. These changes have also led to changes in how mufasirs interpret the Qur'an. The study concluded that because tafsir ra'yi was forbidden, the mufasirs eventually developed tafsir ma'tsur. The concept and practice of tafsir ma'tsur tafsir have changed four times due to changes in the interpretation of the hadith of anti-tafsir ra'yi.